2015
DOI: 10.1109/tuffc.2014.006969
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity focused ultrasound monitoring using harmonic motion imaging for focused ultrasound (HMIFU) under boiling or slow denaturation conditions

Abstract: Harmonic Motion Imaging for Focused Ultrasound (HMIFU) is a recently developed High-Intensity Focused Ultrasound (HIFU) treatment monitoring method that utilizes an amplitude-modulated therapeutic ultrasound beam to induce an oscillatory radiation force at the HIFU focus and estimates the focal tissue displacement to monitor the HIFU thermal treatment. In this study, the performance of HMIFU under acoustic, thermal and mechanical effects were investigated. The performance of HMIFU was assessed in ex vivo canin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Furthermore, relative low-energy HIFU with long exposure time was used in the present study to induce slow tissue denaturation. Our group has demonstrated the feasibility of HMI in monitoring high-energy HIFU treatment with tissue boiling in ex vivo tissue [37][28]. Future studies will explore the feasibility of in vivo HMI monitoring for HIFU treatment with boiling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, relative low-energy HIFU with long exposure time was used in the present study to induce slow tissue denaturation. Our group has demonstrated the feasibility of HMI in monitoring high-energy HIFU treatment with tissue boiling in ex vivo tissue [37][28]. Future studies will explore the feasibility of in vivo HMI monitoring for HIFU treatment with boiling.…”
Section: Discussionmentioning
confidence: 99%
“…A brief description of these two systems is as follows. For more details, please refer to our group's previous publications [28][29]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of this study lies in the fact that only slow denaturation induced ablation was included in the study. However, previous work (Hou et al 2015) from our group has shown that HMIgFUS is robust under faster treatments such as boiling in monitoring the lesion formation in the presence of strong cavitation events with good displacement contrast across the entire treatment window. The present study may have the potential to be applied on cavitation induced HIFU treatment in the future.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the increase in attenuation can occur during thermal lesioning (Zderic et al 2004), resulting in increased absorption therefore increased radiation force within the stiffer lesioning area. However, it has been shown that the decrease in displacement amplitude occurs approximately after reaching 60°C due to the combined effect of viscoelasticity changes and lesion growth overpowering the effect of attenuation (Suomi et al 2016, Hou et al 2015). The increased radiation force during ablation may generate an opposite lesion-to-background contrast by generating higher HMI displacement inside the lesion, which was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%